Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1136/heartjnl-2019-316349
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intervention improves quality of life in older adults after myocardial infarction: randomised clinical trial

Abstract: ObjectiveTo establish the benefits of an early, tailored and low-cost exercise intervention in older patients hospitalised for acute coronary syndrome (ACS).MethodsThe study was a multicentre, randomised assessment of an exercise intervention in patients with ACS ≥70 years with reduced physical performance (as defined by the short physical performance battery (SPPB), value 4–9). The exercise intervention included four supervised sessions (1, 2, 3, 4 months after discharge) and home-based exercises. The control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 22 publications
2
40
0
2
Order By: Relevance
“…These appear particularly low for older adults. However, recently Campo et al reported an early, low cost model with very promising results in terms of physical performance after myocardial infarction and quality of life [66,67]. Our findings for caregivers are consistent with Ebbesen et al [68], who identified that caregivers often have poor emotional and physical health-related quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…These appear particularly low for older adults. However, recently Campo et al reported an early, low cost model with very promising results in terms of physical performance after myocardial infarction and quality of life [66,67]. Our findings for caregivers are consistent with Ebbesen et al [68], who identified that caregivers often have poor emotional and physical health-related quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…The included studies were conducted across 17 countries, including Europe, ( Edelmann et al, 2011 ; Nolte et al, 2015 ; Pibernik-Okanovic et al, 2015 ; Oerkild et al, 2012 ; Hinrichs et al, 2016 ; Koukouvou et al, 2004 ; Bernocchi et al, 2018a ; Campo et al, 2020 ; Asa et al, 2012 ; Kulcu et al, 2007 ; Rodriguez-Manas et al, 2019 ) USA ( Blumenthal et al, 2012a ; de Groot et al, 2019 ; Gary et al, 2012 , 2010 ; Gary et al, 2004 ; Gretebeck et al, 2019 ; Schneider et al, 2016 ; Blumenthal et al, 2012b ), Australia ( Leung et al, 2013 ), and Asia ( Leung et al, 2019 ; Keihani et al, 2014 ; Abdelbasset et al, 2019 ; Soliman and Abdelbasset, 2019 ). The characteristics of the included studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Aerobic exercise was the most commonly applied type of exercise therapy (n = 11), ( Oerkild et al, 2012 ; Asa et al, 2012 ; Kulcu et al, 2007 ; Blumenthal et al, 2012a ; de Groot et al, 2019 ; Gary et al, 2010 , 2004 ; Blumenthal et al, 2012b ; Keihani et al, 2014 ; Abdelbasset et al, 2019 ; Soliman and Abdelbasset, 2019 ) followed by exercise programmes combining aerobic, strengthening, balance and flexibility exercises (n = 8), ( Edelmann et al, 2011 ; Nolte et al, 2015 ; Pibernik-Okanovic et al, 2015 ; Hinrichs et al, 2016 ; Koukouvou et al, 2004 ; Campo et al, 2020 ; Gary et al, 2012 ; Schneider et al, 2016 ; Bernocchi et al, 2018b ), and Tai Chi (n = 2) ( Leung et al, 2013 , 2019 ), or resistance training alone (n = 2), ( Rodriguez-Manas et al, 2019 ; Gretebeck et al, 2019 ). All the included trials provided total or partial supervision of the exercise sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, adherence to the recommended home program was not determined, and thus, a causal relationship between the "dose" of PA and the WS improvement is not possible. However, we recently demonstrated in a randomized controlled trial in older outpatients with CVD that the intervention produced significant increase in habitual PA, associated with improved health outcomes [65][66][67].…”
Section: Limitations Of the Studymentioning
confidence: 99%